Combinatorial release of dexamethasone and amiodarone from a nano-structured parylene-C film to reduce perioperative inflammation and atrial fibrillation. Issue 7 (3rd February 2016) - Robinson, Erik; Kaushal, Sunjay; Alaboson, Justice; Sharma, Sudhish; Belagodu, Amogh; Watkins, Claire; Walker, Brandon; Webster, Gregory; McCarthy, Patrick; Ho, Dean
Abstract : Suppressing perioperative inflammation and post-operative atrial fibrillation requires effective drug delivery platforms (DDP). Abstract : Suppressing perioperative inflammation and post-operative atrial fibrillation requires effective drug delivery platforms (DDP). Localized anti-inflammatory and anti-arrhythmic agent release may be more effective than intravenous treatment to improve patient outcomes. This study utilized a dexamethasone (DEX) and amiodarone (AMIO)-loaded Parylene-C (PPX) nano-structured film to inhibit inflammation and atrial fibrillation. The PPX film was tested in an established pericardial adhesion rabbit model. Following sternotomy, the anterior pericardium was resected and the epicardium was abraded. Rabbits were randomly assigned to five treatment groups: control, oxidized PPX (PPX-Oxd), PPX-Oxd infused with DEX (PPX-Oxd[DEX]), native PPX (PPX), and PPX infused with DEX and AMIO (PPX[AMIO, DEX]). 4 weeks post-sternotomy, pericardial adhesions were evaluated for gross adhesions using a 4-point grading system and histological evaluation for epicardial neotissue fibrosis (NTF). Atrial fibrillation duration and time per induction were measured. The PPX[AMIO, DEX] group had a significant reduction in mean adhesion score compared with the control group (control 2.75 ± 0.42 vs. PPX[AMIO, DEX] 0.25 ± 0.42, P < 0.001). The PPX[AMIO, DEX] group was similar to native PPX (PPX 0.38 ± 0.48 vs. PPX[AMIO, DEX] 0.25 ± 0.42, PNS). PPX-Oxd group adhesions were indistinguishable from controls (PPX-Oxd 2.83 ± 0.41 vs. control 2.75 ± 0.42, PNS). NTF was reduced in the PPX[AMIO, DEX] group (0.80 ± 0.10 mm) compared to control (1.78 ± 0.13 mm, P < 0.001). Total duration of atrial fibrillation was decreased in rabbits with PPX[AMIO, DEX] films compared to control (9.5 ± 6.8 s vs. 187.6 ± 174.7 s, p = 0.003). Time of atrial fibrillation per successful induction decreased among PPX[AMIO, DEX] films compared to control (2.8 ± 1.2 s vs. 103.2 ± 178 s, p = 0.004). DEX/AMIO-loaded PPX films are associated with reduced perioperative inflammation and a diminished atrial fibrillation duration. Epicardial application of AMIO, DEX films is a promising strategy to prevent post-operative cardiac complications.